Distribution of Small Pelagic fish in the Makassar Strait in Relation to Oceanographic Parameters: Distribusi Ikan Pelagis Kecil di Selat Makassar Kaitannya Dengan Parameter Oseanografi - Rini Sahni Putri; Surianti; Hasrianti; Muhammad Bibin; Damis; Fadel Muhammad (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2021)
Fisheries resources that are open access allow overfishing to occur if not handled properly. To prevent this from happening, proper management and utilization of various types of marine resources is necessary. Information on fish distribution is one of the important things in an effort to find the best way in fisheries management. This paper tries to study the distribution of small pelagic fish in relation to oceanographic parameters that affect the movement of fish in the Makassar Strait using remote sensing satellite methods. This research was conducted in May-July 2021 in Makassar Strait waters. The data used in this study are point data and catches of small pelagic fish and oceanographic parameters from remote sensing satellite data. These data were then analyzed using GAM analysis. The results of this study indicate that oceanographic parameters have an influence on catches, in the SST range of 29.5°C – 30.5°C and CHL in the CHL range of 0.5 mg/m3 - 0.8 mg/m3 have a strong influence on the catch of small pelagic fish. The highest average catch was 44.4 kg of small pelagic fish in June.